Sustainable promotion of farmers’ work performance: servant leadership insights from Chinese agricultural entities - Jiannan Wang; Lezhu Zhang; Ruisi Zhang; Shaoning Zhang (Frontiers in Sustainable Food Systems, 2025)
As China’s agricultural sector modernizes, enhancing farmers’ sustainable work performance remains pivotal. This study examines how Servant Leadership directly and indirectly improves productivity in emerging agricultural entities, with Organizational Identity serving as a critical mediator. Structural equation modeling reveals two direct pathways: Altruism (β = 0.124), where leaders prioritize farmers’ well-being through equitable resource allocation and personalized support, fostering trust and reducing attrition; and Social Responsibility (β = 0.198), where ethical practices and community-driven programs align organizational goals with societal welfare, motivating environmentally conscious productivity. Indirectly, Servant Leadership strengthens performance by building farmers’ Organizational Identity (β = 0.613). Three mechanisms drive this: (1) Emotional Soothing (β = 0.370), where empathetic leaders mitigate job stress through open dialog, enabling farmers to focus on collaborative tasks; (2) Persuasive Guidance (β = 0.304), which harmonizes personal and organizational objectives via participatory decision-making, boosting intrinsic motivation; and (3) Leadership Wisdom (β = 0.270), where leaders’ strategic adoption of innovations equips farmers with skills to navigate market risks. By addressing farmers’ developmental needs and nurturing belonging, Servant Leadership cultivates a loyal, adaptive workforce. These findings demonstrate that integrating ethical governance, emotional support, and technology-driven guidance can sustainably elevate agricultural productivity while retaining talent. The study provides actionable insights for policymakers to develop leadership frameworks that balance productivity with farmer welfare, advancing China’s agrarian modernization goals. This human-centric approach underscores the role of leadership in harmonizing economic growth and social equity within transitional agricultural systems.